Reference values and determinants for handgrip strength in healthy subjects - Budziareck, Michele Berçôt; Pureza Duarte, Rodrigo Roig; Barbosa-Silva, Maria Cristina G. (Clinical nutrition (Edinburgh, Scotland), 2008)
To determine reference values and associated factors for handgrip strength among healthy adults. Three hundred well nourished (SGA category A) subjects were studied, aged 18–90 years. Handgrip strength (HS) was determined using a hand dynamometer. Adductor pollicis muscle (APM) thickness and other anthropometric variables were also measured. Results were analyzed according to gender and age group. We carried out multiple linear regression in order to identify significant determinants of handgrip strength. HS is significantly associated with gender and decreases after age 60 years ( p < 0.001). Different reference values for each gender and age category are presented, for both dominant (DHS) and non-dominant hands (NDHS). APM showed a strong correlation with HS ( R 2 = 0.71 and 0.70, for DHS and NDHS, respectively). This association remained significant after adjustment for other variables such as gender, age and body mass index. Reference values are needed to allow the use of HS as a muscular function assessment tool. Values should be stratified by gender and age group. The combined use of HS and APM may be useful as a method for nutritional assessment.